Transcription Factors BARX1 and DLX4 Contribute to Progression of Clear Cell Renal Cell Carcinoma via Promoting Proliferation and Epithelial–Mesenchymal Transition - Sun, Guoliang; Ge, Yue; Zhang, Yangjun; Yan, Libin; Wu, Xiaoliang; Ouyang, Wei; Wang, Zhize; Ding, Beichen; Zhang, Yucong; Long, Gongwei; Liu, Man; Shi, Runlin; et al. (Frontiers in Molecular Biosciences, 2021)
Dysregulation of transcription factors (TFs) contributes to the carcinogenesis and progression of cancers. However, their roles in clear cell renal cell carcinoma (ccRCC) remain largely unknown. This study aims to evaluate the clinical significance of TFs and investigate their potential molecular mechanisms in ccRCC. Data were accessed from the Cancer Genome Atlas Kidney Clear Cell Carcinoma cohort. Bioinformatics algorithm was used in copy number alterations (CNAs), mutations, and differentially expressed TFs analysis. Univariate and multivariate cox regression were performed to identify clinically significant TFs and construct a six-TF prognostic panel. TFs expression was validated in human tissues. Gene set enrichment analysis (GSEA) was utilized to find enriched cancer hallmark pathways. Functional experiments were conducted to verify the cancer-promoting effect of BARX homeobox 1 (BARX1) and distal-less homeobox 4 (DLX4) in ccRCC and western blot was performed to explore their downstream pathways. As for results, many CNAs and mutations were identified in transcription factor (TF) genes. TFs were differentially expressed in ccRCC. An applicable predictive panel of six-TF genes was constructed to predicting overall survival for ccRCC patients, and its diagnostic efficiency was evaluated by the area under the curve (AUC). BARX1 and DLX4 were associated with poor prognosis, and they could promote the proliferation and migration of ccRCC. In conclusion, the six-TF panel can be used as a prognostic biomarker for ccRCC patients. BARX1 and DLX4 play oncogenic roles in ccRCC via promoting proliferation and epithelial-mesenchymal transition. They have the potential to be novel therapeutic targets for ccRCC.